Perancangan Gim Simulasi Perakitan Komputer menggunakan Metode 7 Steps For Designing Serious Games - Mohammad Alauddin; Tri Afirianto; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The computers technological development is increasing in recent times and become major need in various fields, such as institution, education, government or public in general. Every year, computers and the components always evolve also followed by the increasing price. Therefore, choosing a computer and the components based on user spesification and need is really important. However, many people have no basic knowledge about components on a computer. Previously there were studies that could impart student knowledge by using a game. The studies using a 7 steps for designing serious games method. It's undeniable at this time that games can also use in many things not only entertainment purposes. Games that can provide knowledges to game players and give other purpose than only entertaining classified as a serious game. Therefore, a computer assembly simulation games designed by using the 7 step for designing serious game method. The 7 steps for designing serious game method used for found out the need and goals of players based on quality control by cognitive experts therefore the results of designing this game can fulfill the players wishes. This study examines game player needs, game design, game implementation, testing and game evaluation. Based on usability testing on the satisfaction aspect, the average value obtained based on positive experience is 3.41 from 20 respondents, as a consequence, it reflects that the game could be played easily by the game player. While on validation test, the average value obtained is 79.2 from 5 cognitive experts, which indicates that developed game certainly belongs in serious game type.